Analysis on Rock Burst Risks and Prevention of a 54 m-Wide Coal Pillar for Roadway Protection in a Fully Mechanized Top-Coal Caving Face - Zhihua Li; Ke Yang; Jianshuai Ji; Biao Jiao; Xiaobing Tian (Shock and Vibration)
A case study based on the 401103 fully mechanized caving face in the Hujiahe Coal Mine was carried out in this research to analyze the rock burst risks in a 54 m-wide coal pillar for roadway protection. Influencing factors of rock burst risks on the working face were analyzed. Stress distribution characteristics on the working face of the wide coal pillar for roadway protection were discussed using FLAC3D numerical simulation software. Spatial distribution characteristics of historical impact events on the working face were also investigated using the microseismic monitoring method. Results show that mining depth, geological structure, outburst proneness of coal strata, roof strata structure, adjacent mining area, and mining influence of the current working face are the main influencing factors of rock burst on the working face. Owing to the collaborative effects of front abutment pressure of the working face and lateral abutment pressure in the goaf, the coal pillar is in the ultimate equilibrium state and microseismic events mainly concentrate in places surrounding the coal pillars. Hence, wide coal pillars become the regions with rock burst risks on the working face. The working face adopts some local prevention technologies, such as pressure relief through presplitting blasting in roof, pressure relief through large-diameter pores in coal seam, coal seam water injection, pressure relief through large-diameter pores at bottom corners, and pressure relief through blasting at bottom corners. Moreover, some regional prevention technologies were proposed for narrow coal pillar for roadway protection, including gob-side entry, layer mining, and fully mechanized top-coal caving face with premining top layer.